An assessment Model for Customer Relationship Management Process in Iranian Private-Commercial Banks - Tahmoures Hasangholi Pour; Seyed Reza Seyed Javadin; Ahmad Roosta; amir khanlari (Journal of Information Technology Management)
According to several reports, in spite of huge investment on customer relationship management (CRM), risk of implementing such projects is high. One of failure factors is having no method to assess CRM success comprehensively. Nowadays, classic financial methods are common ways for assessing marketing and CRM initiatives. But, the mentioned models are unsuitable to assess investments like CRM that we expect to have intangible, indirect and strategic benefits. So, we need a process-oriented approach to assess all tangible and intangible factors of CRM process and complete existing models. In this paper, using a qualitative approach and grounded theory, a comprehensive and process-oriented CRM assessment model will be provided that considers all factors of customer relationship management in private-commercial banks of Iran. Finally, based on analysis of developed model, some suggestions will be offered for banking managers and future researchers.